Sulfated galactofucan from Sargassum thunbergii induces senescence in human lung cancer A549 cells. Issue 5 (18th May 2020) - Bao, Yizhong; He, Xinyue; Wu, Wanli; Wang, Sanying; Dai, Jihuan; Zhang, Zhongshan; Jin, Weihua; Yan, Jing; Mao, Genxiang
Abstract : Our data indicated that a sulfated galactofucan (SWZ-4-H) from Sargassum thunbergii could induce lung cancer cell senescence by regulating p53, p21, p16, and p-Rb. Abstract : Isolated compounds from Sargassum thunbergii ( S. thunbergii ) have shown to exhibit diverse biological activities, including anti-cancer activity. In this study, we examined the effect of sulfated galactofucan (SWZ-4-H), which was successfully isolated from S. thunbergii, and its underlying mechanism on human lung cancer (LC) A549 cell growth in vitro and in vivo . In vitro experiment indicated that SWZ-4-H decreased cell growth and number in a dose-dependent manner ( P < 0.05 vs. control). Besides, cells treated with SWZ-4-H had irregular morphology, including increased cell volumes, and large nuclei, which suggested senescence-like changes. Moreover, SWZ-4-H increased senescence-related β-galactosidase (SA-β-Gal) staining in a dose-dependent manner; however, while lower (1 mg mL −1 ) concentration induced mainly senescence without causing cell death, higher dosage (3 mg mL −1 ) induced both senescence and cell death. The effect of SWZ-4-H was further confirmed by analyzing the expression of p53, p21, p16, and Rb (p-RB); SWZ-4-H significantly increased the expression of p53, p21, and p16 and decreased phosphorylated Rb (p-RB) in a dose-dependent manner. Moreover, in vivo experiment showed that SWZ-4-H significantly reduced the tumor volume without affecting the body weight. To sum up, our data indicated that SWZ-4-H could induce lung cancer senescence by regulating p53, p21, p16, and p-Rb, thus providing a novel perspective on anti-cancer mechanisms of SWZ-4-H in human lung cancer A549 cells.